Adapting an HIV/STDs Prevention Curriculum to Fit the Needs of Women With Alcohol Problems - CHOI, Y. JOON (2011)
Alcohol and drug dependent women are at increased risk for HIV/STDs. This paper discusses how a prevention curriculum, “Safer Sex Skill Building” (SSB), designed to reduce the contraction of HIV/STDs among drug-abusing women, could be modified to fit the needs of alcohol-abusing women in a residential treatment program. Authors modified the SSB by incorporating feedback from expert consultants as well as by engaging study participants in revising the therapy manual in order to create a curriculum that speaks to participants’ experiences. Specific steps to assist those who would want to adapt an empirically-based manual-driven treatment intervention are provided.